An investigation of the effect of Tetrahydrocannabinol on the viability of cortical neurons - Downer, Eric J. (Trinity College (Dublin, Ireland). Department of Physiology, 2005)
Δ9-Tetrahydrocannabinol (THC), the principle psychoactive component of marijuana (Cannabis sativa), elicits diverse psychological effects in humans. THC exerts its central effects through the CB1 cannabinoid receptor, a G- protein-coupled receptor distributed throughout the central nervous system. We report that THC induces DNA fragmentation in a dose- and time-dependent manner in cultured cortical neurons. THC-induced apoptosis was inhibited by the CB1 receptor antagonist AM 251, suggesting that THC-induced neurotoxicity in cortical neurons is mediated by the central CB1 cannabinoid receptor. THC promoted translocation of mitochondrial cytochrome c to the cytosol and increased the activity of caspase-3, in an AM 251-sensitive manner. Use of the CB1 receptor inhibitor has also identified that cleavage of the DNA-repair enzyme poly(ADP-ribose) polymerase (PARP) as a downstream consequence of THC-induced CB1 activation. Furthermore, THC induced the activation of the stress-activated protein kinase, c-Jun N-terminal kinase (JNK), via the CB1 receptor and its associated G-protein, Gj i/o. Treatment of cultured cortical neurons with THC resulted in the time-dependent activation of JNK1 and JNK2 isoforms that preceded neuronal cell death. Use of specific JNK1 and JNK2 antisense oligonucleotides has identified activation of caspase-3 and DNA fragmentation as a downstream consequence of JNK1 and JNK2 activation. Time course experiments also revealed that THC induces an early increase in the expression of the nuclear phospho-protein, p53. This increase was via the central CB1 receptor and its associated G-protein and was dependent on THC-induced phosphorylation of p53 on residue serine-15. THC was also found to increase the cytosolic expression of the pro-apoptotic mitochondria-associated protein Bax, and induce the phosphorylation of its anti-apoptotic protein partner, Bcl-2, events presumably contributing to cytochrome c translocation and apoptosis. Treatment of cortical neurons with the p53 inhibitor, pifithrin-a, blocked the modulatory effects of THC on Bax and phospho-Bcl-2 protein expression, caspase-3 activity and DNA fragmentation, indicating that p53 neuronal signalling is pivotal in THC-induced neuronal apoptosis of cultured cortical cells.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin